Pre-targeting of polymeric nanomaterials to balance tumour accumulation and clearance. Issue 57 (21st June 2022) - Fletcher, N. L.; Prior, A.; Choy, O.; Humphries, J.; Huda, P.; Ghosh, S.; Houston, Z. H.; Bell, C. A.; Thurecht, K. J.
Abstract : A pre-targeting approach to preserve the stealth surface chemistry of PEGylated nanomedicines during circulation is demonstrated. Abstract : Pre-targeting of bispecific antibodies is probed to enhance tumour retention while limiting clearance of administered multifunctional branched PEGylated nanomedicines. The temporal influence of pre-targeting on polymer interaction with tumour cells and tissue is explored using in vitro assays through to preclinical validation.